Seasonal Food and Feeding Habits of Naziritor chelynoides (Mc Clelland) 1839 of Mardi Khola, Kaski, Nepal - Shrestha, Om Hari; Shreshta, Jiwan (Journal of Natural History Museum, 2009)
The fishes (Naziritor chelynoides) were collected in different months with the help of local devices (cast net and tiyari). The collected specimens were dissected in the laboratory and their gut contents were analyzed dividing food items (dietary items) into different groups viz., algae, diatoms, insects and fragments etc. The gut of fish consisted of different dietary items (plant origin and animal origin) indicating Naziritor chelynoides as an omnivorous fish. The average percentage of algae was found as 27.89 and average percentage of insects, diatoms and fragments were found as 20.15, 19.26 and 3.61 respectively. Water quality analysis of the Mardi khola (study area) revealed that the transparency of the water was crystal clear except in the rainy season. The dissolved oxygen was found in an optimum level (12.65mg/ l). The average temperature of the river was found as 19.12°C and the average pH was found as 8.41 during the study period. Key words: Feeding habits; Mardi Khola; omnivorous; water quality analysis Journal of Natural History Museum Vol. 23, 2008 Page 98-107